Chinese People’s Political Consultative Conference: China’s Practice in Consultative Democracy - Jiayi, Zou (Napredak, 2024)
On the rich soil of 5,000-year long Chinese culture, a great creation of the Communist Party of China and Chinese was built – socialist consultative democracy as the world’s unique and original form of political and cultural organization, in which people govern their country. The aim of this paper is to point to the importance of social dialogue and continued consultations with the people in order to ensure that individuals exercise comprehensive and true rights in the political, economic, cultural and social life. For its realization in practice, it calls for the functioning of a highly inclusive and integrated democratic system in which every idea and talent have an opportunity to develop and be applied in real life. Only in this manner it is possible to realize high development objectives of this great country which, spreading solidarity and democracy, integrates the will of the Party, people and state.
Keywords: dialogue; consultations; tradition; public opinion; people’s democracy